Cow feed and preparation method thereof - TANG FUJIAN (2017)
The invention discloses a cow feed and a preparation method thereof. The cow feed is composed of the following substances by mass: 120-160 parts of silage, 40-80 parts of wheat bran, 45-67 parts of corn, 30-60 parts of pumpkin, 35-55 parts of corn germ meal, 30-60 parts of soybean flour, 20-30 parts of soybean meal, 20-30 parts of chicken breast, 10-15 parts of Fructus Arctii, 6-12 parts of Lolium multiflorum, 10-15 parts of beet pulp, 12-20 parts of a cordyceps militaris medium, 12-20 parts of vinasse, and the balance flour. The cow feed provided by the invention utilizes cheap agricultural and sideline product raw materials containing functional substances, regulates cow rumen microflora while reducing the feed cost, improves the milk yield of cows and the anti-stress ability and immunity of cow bodies, thereby increasing economic benefits. 本发明公开了种奶牛饲料及其制备方法，由以下质量份数的物质组成：青贮120-160份、麦麸40-80份、玉米45-67份、南瓜30-60份、玉米胚芽粕35-55份、大豆粉30-60份、黄豆粉20-30份、鸡胸肉20-30份、牛蒡子10-15份、多花黑麦草6-12份、甜菜粕10-15份、北虫草培养基12-20份、酒糟12-20份、余量为面粉